Efficient Supply of Human Capital: Role of College Major - Sungjin Cho; Jihye Kam; Soohyung Lee (Institute of Labor Economics (IZA), 2017)
This study examines the extent to which changing the composition of college majors among working-age population may affect the supply of human capital or effective labor supply. We use the South Korean setting, in which the population is rapidly aging, but where, despite their high educational attainment, women and young adults are still weakly attached to the labor market. We find that Engineering majors have an advantage in various outcomes such as likelihood of being in the labor force, being employed, obtaining long-term position, and earnings, while Humanities and Arts/Athletics majors show the worst outcomes. We then conduct a back-of-the-envelope calculation of the impact of the recently proposed policy change to increase the share of Engineering majors by 10 percent starting in 2017. Our calculation suggests that the policy change may have a positive but small impact on labor market outcomes.
Keywords: I2; J2; J4; 330; returns to schooling; college major; economics of education; gender gap; human capital; aging